Numerical Study of Convective Heat Transfer in Plain Tubes with Tri-hybrid Nanofluids for Turbulent Flow Regime - Anwar Ilmar Ramadhan; Wan Hamzah Azmi; Raslan A. Alenezi; Efrizon Umar (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2021)
The use of increased heat transfer techniques, can improve the thermal performance of the tubes. Computational fluid dynamics studies have been carried out to study the heat transfer characteristics and friction factor of the Al2O3-TiO2-SiO2 nanofluids-ethylene glycol (EG)/water (W) (40:60) flowing in the plain tube. The three-dimensional turbulent k-ε model that can be realized with enhanced use of heat treatment on the wall is used for turbulent flow regime. The overall evaluation of tubular performance-tested is based on thermo-hydrodynamic performance index. The results showed that behavioural differences depend on the selected parameters to compare tri-hybrid nanofluids with the base fluid. In addition, the heat transfer coefficient increases with the increase in volume concentration of nanoparticles at the same Reynolds number. The friction factor of Al2O3-TiO2-SiO2 nanofluids decreased exponentially with an increase of Reynolds number. The conventional correlations that have been used in turbulent flow regimes to predict heat transfer rates and friction factors are Dittus-Boelter and Blasius correlations, for tubes also apply to tri-hybrid nanofluids tested which assume that tri-hybrid nanofluids have a homogeneous fluid behaviour.